2017
DOI: 10.3390/biomedicines5030039
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells: What Is the Mechanism in Acute Graft-Versus-Host Disease?

Abstract: After more than a decade of preclinical and clinical development, therapeutic infusion of mesenchymal stromal cells is now a leading investigational strategy for the treatment of acute graft-versus-host disease (GVHD). While their clinical use continues to expand, it is still unknown which of their immunomodulatory properties contributes most to their therapeutic activity. Herein we describe the proposed mechanisms, focusing on the inhibitory activity of mesenchymal stromal cells (MSCs) at immunologic checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 117 publications
(130 reference statements)
0
29
0
1
Order By: Relevance
“…The osteogenic differentiation potential of MSCs makes them successful in treating and managing bone fractures [97]. The ability of MSCs to modulate immune responses is considered as a safe and feasible strategy to treat Crohn's disease [98], systemic lupus erythematosus (SLE) [99,100], rheumatoid arthritis (RA) [101], GvHD [102], Type I diabetes [103] and so on. MSCs also prevent allergic airway inflammation and reduce the symptoms of severe asthma [104][105][106][107][108].…”
Section: Therapeutic Properties Of Mscsmentioning
confidence: 99%
“…The osteogenic differentiation potential of MSCs makes them successful in treating and managing bone fractures [97]. The ability of MSCs to modulate immune responses is considered as a safe and feasible strategy to treat Crohn's disease [98], systemic lupus erythematosus (SLE) [99,100], rheumatoid arthritis (RA) [101], GvHD [102], Type I diabetes [103] and so on. MSCs also prevent allergic airway inflammation and reduce the symptoms of severe asthma [104][105][106][107][108].…”
Section: Therapeutic Properties Of Mscsmentioning
confidence: 99%
“…Evidence from in vitro studies and animal models indicates that bone marrow-derived MSCs have immunosuppressive and immunomodulatory functions [13][14][15][16][17][18][19]. Allogeneic tolerance, inhibition at immune checkpoints, and paracrine signaling are MSC mechanisms particularly relevant to aGVHD [20,21]. Results from initial clinical studies of MSCs have indicated favorable clinical response rates with an acceptable safety profile when used to treat steroid-refractory GVHD (SR-aGVHD) [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), acting as a pleiotropic immune regulator, are reported to suppress immune processes, in which nearly all immune cells including T cells, natural killer (NK) cells, B cells, and dendritic cells (DCs) are affected [4,[6][7][8][9]. In the recent years, more attention has paid to potential efficiency of MSCs in aGvHD as they show low toxicity and high expansion in vitro [5,10]. The immunomodulatory effects of MSCs are not always immunosuppressive as it is depending on inflammatory microenvironments [11][12][13].…”
Section: Introductionmentioning
confidence: 99%